2013
DOI: 10.1136/annrheumdis-2012-eular.2229
|View full text |Cite
|
Sign up to set email alerts
|

THU0264 Adalimumab significantly reduces recurrence rate of anterior uveitis in patients with ankylosing spondylitis

Abstract: Background A high percentage (30-40%) of patients with Ankylosing Spondylitis (AS) suffer from acute anterior uveitis (AAU) attacks. Local treatment with corticosteroids is a beneficial treatment. In addition, there are suggestions that TNF blocking agents also decrease the recurrence rate of AAU attacks. However, proper prospective studies investigating the effectiveness of anti-TNF treatment on the recurrence rate of AAU attacks in AS are lacking. Objectives To examine whether the use of adalimumab decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Among anti-TNF mAb, ADA has been shown to significantly reduce the risk of non-infectious uveitic flare, associated or not with axSpA, in two placebo-controlled RCTs [5,6]. Several observational studies and post-hoc analysis from placebo-controlled studies focused on axSpA-associated AAU and showed that the incidence of AAU decreases after treatment with anti-TNF mAb compared to the incidence before treatment [7][8][9][10][11][12][13]. These studies mainly involved IFX and ADA.…”
Section: Introductionmentioning
confidence: 99%
“…Among anti-TNF mAb, ADA has been shown to significantly reduce the risk of non-infectious uveitic flare, associated or not with axSpA, in two placebo-controlled RCTs [5,6]. Several observational studies and post-hoc analysis from placebo-controlled studies focused on axSpA-associated AAU and showed that the incidence of AAU decreases after treatment with anti-TNF mAb compared to the incidence before treatment [7][8][9][10][11][12][13]. These studies mainly involved IFX and ADA.…”
Section: Introductionmentioning
confidence: 99%